STUDENTS' ENGAGEMENT IN ONLINE ENGLISH LEARNING: FACTORS AND PEDAGOGICAL STRATEGIES - Tina Sheba Cornelia Sitompul; Ulfah Sari Rezeki (Sensei International Journal of Education and Linguistic, 2026)
Since the pandemic many schools and universities use online learning, but the problem is the students are often not active. They open the class but they do not turn on the camera, do not answer, and sometimes they leave the meeting. This article discusses students' engagement in online English learning, the factors and the pedagogical strategies. The method used is literature review from journals about engagement and online learning. The result shows that the engagement of the students is influenced by the teacher, the task, the interaction with the friends, the internet connection, and also the motivation of the students themselves. Therefore the teacher must design the online class so that the students have something to do and not only listen.